Changes and interactions between forest landscape connectivity and burnt area in Spain - Martín-Martín, Carmen; Bunce, Robert G H; Saura, Santiago; Elena-Rosselló, Ramón (Ecological Indicators, 2013)
The spatial structure, functionality and dynamics of forest landscapes in peninsular Spain and the Balearic Islands were compared over the last five decades. Two particular features were studied in the sample sites: forest connectivity for wildlife and areas burnt by wildfires. 191 Squares, each 4 km × 4 km, were selected from the SISPARES (the monitoring framework designed to evaluate the trends in the structure of Spanish rural landscapes) environmental strata. Aerial photographs from 1956, 1984, 1998 and 2008 were interpreted and 11 land cover categories mapped and checked in the field, using a minimum mapping area of one hectare. The Equivalent Connected Area Index was used to assess forest connectivity over the sampling period. Social and economical factors were assessed using indicators of farm intensiveness. The Spanish forest connectivity has improved in the last five decades although two different trends can be identified: the first 40 years are characterized by positive rates of growth whereas the 10 last years are characterized by their stability. Nevertheless the area of burnt land was higher along the first 25 studied years and decreased significantly over the last decade. Our results show the climate is the main driver in the evolution of forest connectivity and burnt area in the forest landscapes, playing a direct role on forest biomass production and wildfire ignition and propagation, as well as an indirect role by keeping vertical and horizontal forest continuity through the landscape spatial pattern. Social and economic factors are very important drivers as well: Rural population density and farm size average have been tested as good indicators of landscape artificiality, highly correlated to wildfire hazard and forest connectivity. Finally, we have pointed out the evolutionary path followed by SISPARES framework as a tool for monitoring rural landscapes. It emphasises on the requirement of a 30 years time window for building-up reliable dynamic multifunctional model. ©
Keywords: Conefor-Sensinode; Ecological connectivity; Farm intensiveness; landscape dynamics; Rural population density; Sispares; Spatial pattern indicators; wildfire occurrence

Effects of silviculture on native tree species richness: interactions between management, landscape context and regional climate - Martín-Queller, Emi; Diez, Jeffrey M; Ibáñez, Inés; Saura, Santiago (Journal of Applied Ecology, 2013)
* Patterns of forest biodiversity are shaped by a complex set of processes operating over different spatial scales. Climate may largely determine species richness at regional scales, but biotic interactions and disturbance events are known to be important at local scales. The interactions between these local and regional processes are poorly understood, complicating efforts to manage for biodiversity. * In this study, we used Spanish forest inventory data, together with hierarchical Bayesian models, to analyse how different harvest intensities affect patterns of species richness in a 152 000 km2 area in central Spain. Particularly, we quantified the interacting effects of locally applied silvicultural disturbances, of those applied in the surrounding landscape, and of the regional climate on native tree species richness. * Our study supports the overall hypothesis that a hierarchical set of processes influence species richness, with regional climate contributing to shape the impacts of local harvesting practices and other environmental variables (topography and productivity). * In particular, we found that partial harvesting in both coniferous and broad-leaved Mediterranean forests may support greater tree species richness than complete harvesting and no management. However, this effect depended on the ecosystem and the surrounding landscape, being much less likely in semi-arid regions under water stress conditions and in landscapes dominated by managed forests (and particularly by completely harvested stands). * In general, forest stands exhibited increased tree species richness when surrounded by species-rich riparian forests, probably due to metacommunity dynamics and/or ecological history (land uses) of the area. * Synthesis and applications. The effects of forest management on local species richness were shaped by coarse climate conditions and by the type and extent of other management practices in the surrounding landscapes. Therefore, to develop effective forestry management plans that optimize local diversity, we need to (i) apply regionally tailored practices with lower harvest intensities in areas of greater hydric stress; (ii) avoid the extensive application of a single silvicultural system over large areas and (iii) preserve a mosaic of species-rich forests that can act as sources of colonizers to enrich the regenerating stands nearby.
Keywords: Biodiversity; Disturbance ecology; hierarchical Bayes; intermediate disturbance hypothesis; landscape ecology; Mediterranean forests; metacommunity dynamics; partial harvesting; spatial scale